Linking Adverbials in Indonesian EFL Students’ Essays: A Corpus-Driven Study - Ikmi Nur Oktavianti; Japen Sarage (Institut Agama Islam Negeri Palopo, 2022)
Writing is the activity of arranging and organizing ideas that need some logical connectors to make the ideas cohesively structured. There are several plausible means for cohesiveness, including linking adverbials (LAs). This study examines the LA categories found in EFL students’ academic essays and explores how EL students use them. The data were collected from students’ essays compiled as a learner corpus, Learner Corpus of Academic Writing, comprising 52,404 words. The present study employed LancsBox as the corpus tool and The Louvain Corpus of Native English Essays as the control corpus to assist the analysis. The study results show that all primary categories of LAs are found in the corpus. However, the subcategory transition to another topic is absent from the corpus. In the frequency of use, causal resultative LAs outnumber all other categories, followed by additive and adversative LAs. As for the least frequent LAs, the study identified sequential types. In comparison to the native writer corpus, it is found that there are shared similarities, including the categories and the subcategories of LAs found in both corpora. Regarding the frequency of use, the most frequent types are relatively similar with different positions, namely causal resultative and additive LAs, while the least frequent type is sequential. These results suggest more considerations in designing writing materials, especially in regard to transition markers belonging to the sequential category.